Triterpenoids from Pouteria campechiana (H.B.K.) Baehni - Labaclado, Lynne Maddatu (Animo Repository, 2007)
The ethyl acetate extract of the stem bark of Pouteria campechiana (H.B.K.) Baehni afforded spinasterol (PC19) and three fatty acid esters of triterpenes: erythrodiol (PC3), betulinic acid (major compound of PC11) and oleanolic acid (minor compound of PC11). The last two were obtained as a mixture (3:1). The structures of PC3 and PC11 were elucidated through extensive 1-D and 2-D NMR analyses. On the other hand, PC19 was identified through a comparison of its 1H NMR spectral data with the one found in the literature. Antimicrobial test results indicated that PC3 has a low activity against Escherichia coli, Candida albicans, Trichophyton mentagrophytes, Pseudomonas aeruginosa and Staphylococcus aureus. It was found to be inactive against Bacillus subtilis and Aspergillus niger. On the other hand, PC11 has a low activity against Escherichia coli, Pseudomonas aeruginosa, Candida albicans and Trichophyton mentagrophytes. It was inactive against Staphylococcus aureus, Bacillus subtilis and Aspergillus niger.